2002
DOI: 10.3201/eid0807.010277
|View full text |Cite
|
Sign up to set email alerts
|

First Human Isolate of Hantavirus (Andes virus) in the Americas

Abstract: We isolated Andes virus (formal name: Andes virus [ANDV], a species in the genus Hantavirus ) , from serum of an asymptomatic 10-year-old Chilean boy who died 6 days later of hantavirus pulmonary syndrome (HPS). The serum was obtained 12 days after his grandmother died from HPS and 2 days before he became febrile. No hantavirus immunoglobulin (Ig) G or IgM antibodies were detected in the serum sample. After three blind passages, ANDV antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 22 publications
1
55
0
4
Order By: Relevance
“…Some of the negative RT-PCR assays may indicate sample collection after rapid viral clearance in a mild infection. As noted in one Andes virus infection, 20 the absence of IgM-positive assays in the presence of positive PCR assays may represent very early infection. The lack of follow-up samples also prevents unequivocable diagnosis in those subjects without IgG serology performed.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the negative RT-PCR assays may indicate sample collection after rapid viral clearance in a mild infection. As noted in one Andes virus infection, 20 the absence of IgM-positive assays in the presence of positive PCR assays may represent very early infection. The lack of follow-up samples also prevents unequivocable diagnosis in those subjects without IgG serology performed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study showed that viral RNA could be detected in peripheral blood cells for up to 2 weeks before the onset of symptoms 15 and the infectious virus was isolated from a seronegative, asymptomatic child 2 days before he developed HCPS. 18 Thus, the virus could be spread by asymptomatic patients to other parts of the world. However, an influenza-like pandemic scenario seems to be unlikely because human-to-human transmission of ANDV appears to be very inefficient, occurs mainly within households, and requires relatively intimate interpersonal contact.…”
Section: Human Adaptive Immune Responses To Hantavirusesmentioning
confidence: 99%
“…We report here the complete genomic sequence of the Chilean ANDV CHI-7913, whose isolation from a 10-year-old HPS patient has been recently described (Galeno, et al, 2002). A preliminary account of this work has been reported (Tischler et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Andes virus used in this study was isolated from a 10-year-old patient who died of HPS (ANDV CHI-7913) and has been described previously (Galeno et al, 2002). Vero E6 cells were originally provided by Dr. B. Hjelle, and were grown in Eagles minimal essential medium (MEM).…”
Section: Virus Cells and Mediamentioning
confidence: 99%